Glucopyranosyl lipid A adjuvant significantly enhances HIV specific T and B cell responses elicited by a DNA-MVA-protein vaccine regimen. - Paul F McKay; Alethea V Cope; Jamie F S Mann; Sarah Joseph; Mariano Esteban; Roger Tatoud; Roger Tatoud; Darrick Carter; Steven G Reed; Jonathan Weber; Robin J Shattock (PLoS ONE)
Using a unique vaccine antigen matched and single HIV Clade C approach we have assessed the immunogenicity of a DNA-poxvirus-protein strategy in mice and rabbits, administering MVA and protein immunizations either sequentially or simultaneously and in the presence of a novel TLR4 adjuvant, GLA-AF. Mice were vaccinated with combinations of HIV env/gag-pol-nef plasmid DNA followed by MVA-C (HIV env/gag-pol-nef) with HIV CN54gp140 protein (+/-GLA-AF adjuvant) and either co-administered in different muscles of the same animal with MVA-C or given sequentially at 3-week intervals. The DNA prime established a population of B cells that were able to mount a statistically significant anamnestic response to the boost vaccines. The greatest antigen-specific antibody response was observed in animals that received all vaccine components. Moreover, a high proportion of the total mucosal IgG (20 - 50%) present in the vaginal vault of these vaccinated animals was vaccine antigen-specific. The potent elicitation of antigen-specific immune responses to this vaccine modality was also confirmed in rabbits. Importantly, co-administration of MVA-C with the GLA-AF adjuvanted HIV CN54gp140 protein significantly augmented the antigen-specific T cell responses to the Gag antigen, a transgene product expressed by the MVA-C vector in a separate quadriceps muscle. We have demonstrated that co-administration of MVA and GLA-AF adjuvanted HIV CN54gp140 protein was equally effective in the generation of humoral responses as a sequential vaccination modality thus shortening and simplifying the immunization schedule. In addition, a significant further benefit of the condensed vaccination regime was that T cell responses to proteins expressed by the MVA-C were potently enhanced, an effect that was likely due to enhanced immunostimulation in the presence of systemic GLA-AF.